Induction of chondrogenesis of human placenta-derived mesenchymal stem cells via heparin-grafted human fibroblast derived matrix - Noh, Yong Kwan; Ping, Du; Avelino Dos Santos Da Costa; Park, Kwideok (BioMed Central Ltd., 2018)
Background: Formation of mature and functional articular cartilage is still challenging in cartilage tissue engineering. This study investigates the potential of using heparin-grafted decellularized extracellular matrix (ECM) as a novel growth factor delivery platform towards human placenta-derived mesenchymal stem cells (hPMSCs) chondrogenic differentiation. Human fibroblast-derived extracellular matrix (hFDM) is naturally obtained from in vitro-cultured human lung fibroblasts via a mild decellularization process. hFDM was then conjugated with heparin via N-(3-Dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride (EDC) chemistry and subject to transforming growth factor (TGF)-β1 immobilization. Once heparin grafted-hFDM (hFDM-hep) and hPMSCs were co-embedded into collagen gel, they were examined for in vitro and in vivo chondrogenesis of hPMSCs for 4 weeks. Results: We identified heparin moieties on hFDM via toluidine blue O assay and Fourier transform infrared spectroscopy, respectively. We found out that collagen spheroids containing hFDM-hep and TGF-β1 exhibited a sustained release of growth factor for 28 days in vitro. Chondrogenesis of hPMSCs in vitro was supported by accumulated glycosaminoglycan (GAG) content and upregulated chondrogenic specific markers (collagen II, aggrecan, Sox9). Meanwhile, PKH26 - labeled hPMSCs incorporated collagen with either hFDM or hFDM-hep was pre-conditioned in a chondrogenic media for 3 days and subcutaneously implanted in the back of nude mice for 4 weeks. The implanted collagen spheroids containing both hPMSCs and hFDM-hep retained more viable hPMSCs and showed higher level of chondrogenic differentiation, based on immunostaining of collagen type II over collagen alone or Col/hFDM group. In addition, histological examination showed more positive signals of GAG via Safranin-O staining. Conclusion: TGF-β1-immobilized hFDM-hep can provide an appropriate microenvironment for chondrogenic differentiation of hPMSCs in 3D collagen spheroid. ？ 2018 The Author(s).